Effect of Electrical Conductivity on Geotechnical Parameters of Clays - Hadjadj, F.Z.; Laredj, N.; Bendani, K.; Maliki, M.; Missouma, H. (Algerian Journal of Research and Technology (AJRT), 2018)
The use of electrical methods has known in recent year’s significant development in several fields such as geophysics, agriculture, geology, geotechnics ... etc. The main interests of the electrical methods are multiple: possibilities of spatialization of the measurements, the possibility also to acquire data’s in a continuous way in the time; the speed and low cost of the measures. In view of these attractive features, a large number of applications have been developed for electrical measurements in a wide variety of scientific and engineering fields. The mean aim of this work is to establish relationships between electrical conductivity and soil geotechnical parameters such as water content, degree of saturation, porosity and ion concentration. The soil selected for this study is a clay from the region of Ain-Nouissy (Mostaganem).